International prevalence of the use of peripheral intravenous catheters. Issue 8 (3rd June 2015) - Alexandrou, Evan; Ray‐Barruel, Gillian; Carr, Peter J.; Frost, Steven; Inwood, Sheila; Higgins, Niall; Lin, Frances; Alberto, Laura; Mermel, Leonard; Rickard, Claire M.
<x xml:space="preserve">Abstract</x> Over a billion peripheral intravenous catheters (PIVCs) are inserted each year in hospitalized patients worldwide. However, international data on prevalence and management of these devices are lacking. The study assessed the prevalence of PIVCs and their management practices across different regions of the world. This global audit involved 14 hospitals across 13 countries, with 479 patients screened for the presence of a PIVC. We found 59% of patients had at least 1 PIVC in place, and 16% had other types of vascular devices. We also found that overall, 25% of patients had no vascular device in place. The majority of PIVCs were inserted by nursing staff or a specialist team. The prevalence of idle PIVCs in place with no fluid or medication orders was 16%, and 12% of PIVCs had at least 1 symptom of phlebitis. Journal of Hospital Medicine 2015;10:530–533. © 2015 Society of Hospital Medicine